2021
DOI: 10.1111/ane.13558
|View full text |Cite
|
Sign up to set email alerts
|

Fetal posterior cerebral artery configurations in an ischemic stroke versus an unselected hospital population

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…In Koreans (Chung et al, 1980;Chun & Kwun, 1985), the frequency was 8.2 % on the right side, 5.2 % on the left side, and 3.6 % on both sides. In addition, unilateral fetaltype variant of the PCA was significantly more frequent on the right (15 %) than on the left side (8 %) in an angiography study (Frid et al, 2022).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In Koreans (Chung et al, 1980;Chun & Kwun, 1985), the frequency was 8.2 % on the right side, 5.2 % on the left side, and 3.6 % on both sides. In addition, unilateral fetaltype variant of the PCA was significantly more frequent on the right (15 %) than on the left side (8 %) in an angiography study (Frid et al, 2022).…”
Section: Discussionmentioning
confidence: 82%
“…Yang et al (2007) reported that the fetal-type variant of the PCA was more frequently found in the ipsilateral hemisphere of patients with an infarction than in the control group (44.4 % vs 18.5 %) by both diffusion-weighted magnetic resonance imaging (DWI) and cerebral angiography (1388 patients), of which large artery atherosclerosis of the carotid artery was very common in patients with infarction. Recently, Frid et al (2022) reported that the prevalence of any fetal-type variant of the PCA was similar in ischemic stroke patients (31 %) and unselected patients (32 %) with DWI and computed tomography angiography diagnosed with 1953 ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Koreans [3,4], the frequency was 8.2% on the right side, 5.2% on the left side, and 3.6% on both sides. In addition, unilateral fetal-type variant of the PCA was signi cantly more frequent on the right (15%) than on the left side (8%) in an angiography study [5].…”
Section: Discussionmentioning
confidence: 85%
“…Yang et al [21] reported that the fetal-type variant of the PCA was more frequently found in the ipsilateral hemisphere of patients with an infarction than in the control group (44.4% vs 18.5%) by both diffusion-weighted magnetic resonance imaging (DWI) and cerebral angiography (1388 patients), of which large artery atherosclerosis of the carotid artery was very common in patients with infarction. Recently, Frid et al [5] reported that the prevalence of any fetal-type variant of the PCA was similar in ischemic stroke patients (31%) and unselected patients (32%) with DWI and computed tomography angiography diagnosed with 1953 ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether the VLMT and CFT are equivalent regarding their level of difficulty and validity which hampers the assumption that they are ideal tests to compare verbal and figural memory performance. Finally, subgroups of patients with PCA stroke have variable arterial supply patterns [40,41]. This gives rise to atypical infarct distributions [9,42,43] and generates altered collateral circulation and vascular reserve in the hippocampus, thalamus or other regions [44], a fact that should be controlled in future studies.…”
Section: Discussionmentioning
confidence: 99%